Techno-Entrepreneurial Relationship Marketing (TERM) to Enhance Entrepreneurial Competitiveness in Central Java - Jati Nugroho; Azizah, Azizah; Isnaini Nurkhayanti; Sandi Supaya; Dika Vivi Widyanti (International Journal of Education, Vocational and Social Science, 2025)
Techno-Entrepreneurial Relationship Marketing (TERM) has emerged as a critical framework for enhancing the competitiveness of student entrepreneurs in Central Java. This study explores how TERM, which integrates digital technology and relationship marketing, can improve marketing performance and foster long-term competitive advantage. Using a mixed-methods approach, the research surveyed 150 student entrepreneurs across 35 districts in Central Java, assessing the impact of Information Technology Adoption, Entrepreneurial Orientation, and Interaction Proactiveness on Marketing Performance. The findings indicate that TERM significantly enhances marketing performance by enabling proactive customer engagement, rapid responsiveness, and data-driven decision-making. The integration of digital tools such as social media platforms, CRM systems, and data analytics was found to be crucial for improving customer loyalty and market positioning. The study concludes that educational institutions should incorporate TERM into their entrepreneurship curricula to better prepare students for the challenges of digital markets. This approach not only supports the development of entrepreneurial skills but also strengthens the overall competitiveness of student-led businesses, positioning them for long-term success in a rapidly evolving digital economy.